2023
DOI: 10.1093/jee/toac203
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Trunk Injection Into Orchard Trees: Consequences on the Performance and Preference of Hemipteran Pests

Abstract: Apples and pears are among the most widely cultivated fruit species in the world. Pesticides are commonly applied using ground sprayers in conventional orchards; however, most of it will not reach the target plant, increasing the contamination of nontarget organisms such as natural predators, pollinators, and decomposers. Trunk injection is an alternative method of pesticide application that could reduce risks to beneficials and workers. Essential oils represent a ‘green’ alternative to pesticides due to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The longer latency time indicates that aphids were reluctant to probe. Such behavior is usually associated with negative factors located at the plant's surface [34,36], and in our bioassays, it could be explained by the repellent effect of the applied essential oils, which discouraged the aphids from initiating probing. These findings corroborate the relatively high anti-settling activity of yarrow and Santolina oils, which was observed in the choice tests.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The longer latency time indicates that aphids were reluctant to probe. Such behavior is usually associated with negative factors located at the plant's surface [34,36], and in our bioassays, it could be explained by the repellent effect of the applied essential oils, which discouraged the aphids from initiating probing. These findings corroborate the relatively high anti-settling activity of yarrow and Santolina oils, which was observed in the choice tests.…”
Section: Discussionmentioning
confidence: 79%
“…Several authors suggest that lipophilic active compounds of essential oils can penetrate the plant surface, pass into deeper tissue layers, and consequently interfere with aphid-feeding behavior [30,34,37]. The disturbances in the feeding process result in a reduction in nutrient intake and lead to a limitation of aphid development [36,38]. The results of our previous study have shown that essential oils from S. chamaecyparissus and T. patula negatively affected the bionomic parameters of R. padi and M. persicae.…”
Section: Discussionmentioning
confidence: 98%
“…Endotherapy treatment is often used in urban plant protection for deciduous trees. Several experiments have demonstrated the successful use of trunk injection against different pests [21][22][23][24][25]. Walnut trees have been effectively treated with abamectin against the walnut husk fly (Rhagoletis completa) [24].…”
Section: Introductionmentioning
confidence: 99%